2014
DOI: 10.1186/cc13896
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prone positioning on mortality in patients with acute respiratory distress syndrome: a meta-analysis of randomized controlled trials

Abstract: IntroductionProne positioning (PP) has been reported to improve the survival of patients with severe acute respiratory distress syndrome (ARDS). However, it is uncertain whether the beneficial effects of PP are associated with positive end-expiratory pressure (PEEP) levels and long durations of PP. In this meta-analysis, we aimed to evaluate whether the effects of PP on mortality could be affected by PEEP level and PP duration and to identify which patients might benefit the most from PP.MethodsPublications de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 30 publications
1
61
0
4
Order By: Relevance
“…Table 1 demonstrates the most significant relative risk was found for the 60-day hospitalization period in the conditions under study (18) . Statistical significance for the reduction of mortality from prone positioning was verified in six out of the 11 studies included, especially in those in which protective ventilation was used (19) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 demonstrates the most significant relative risk was found for the 60-day hospitalization period in the conditions under study (18) . Statistical significance for the reduction of mortality from prone positioning was verified in six out of the 11 studies included, especially in those in which protective ventilation was used (19) .…”
Section: Resultsmentioning
confidence: 99%
“…The search for relevant studies in gray literature was not contained in the inclusion criteria of three systematic reviews (17)(18)23) . Six studies did not state the conflicts of interest (17)(18)(19)(20)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent meta-analyses have confirmed these findings and additionally suggested that the improved survival from prone positioning is only observed when combined with low tidal volume and high levels of PEEP ventilation. 14 The OSCAR trial, 15 a multicenter randomized study, documented that the use of highfrequency oscillatory ventilation had no significant effect on 30-d mortality in subjects undergoing mechanical ventilation for ARDS.…”
Section: See the Original Study On Page 127mentioning
confidence: 99%